Monomethylfumarate protects against ovariectomy-related changes in body composition. Issue 1 (October 2019) - Bollag, Anna E; Guo, Tianyang; Ding, Ke-Hong; Choudhary, Vivek; Chen, Xunsheng; Zhong, Qing; Xu, Jianrui; Yu, Kanglun; Awad, Mohamed E; Elsalanty, Mohammed; Johnson, Maribeth H; McGee-Lawrence, Meghan E; et al.
Abstract : Osteoporosis, low bone mass that increases fracture susceptibility, affects approximately 75 million individuals in the United States, Europe and Japan, with the number of osteoporotic fractures expected to increase by more than three-fold over the next 50 years. Bone mass declines with age, although the mechanisms for this decrease are unclear. Aging enhances production of reactive oxygen species, which can affect bone formation and breakdown. The multiple sclerosis drug Tecfidera contains dimethylfumarate, which is rapidly metabolized to monomethylfumarate (MMF); MMF is thought to function through nuclear factor erythroid-derived-2-like-2 (NRF2), a transcription factor activated by oxidative stress which induces the expression of endogenous anti-oxidant systems. We hypothesized that MMF-elicited increases in anti-oxidants would inhibit osteopenia induced by ovariectomy, as a model of aging-related osteoporosis and high oxidative stress. We demonstrated that MMF activated NRF2 and induced anti-oxidant NRF2 target gene expression in bone marrow-derived mesenchymal stem cells. Sham-operated or ovariectomized adult female mice were fed chow with or without MMF and various parameters were monitored. Ovariectomy produced the expected effects, decreasing bone mineral density and increasing body weight, fat mass, bone marrow adiposity and serum receptor activator of nuclear factor-kappa-B ligand (RANKL) levels. MMF decreased fat but not lean mass. MMF improved trabecular bone microarchitecture after adjustment for body weight, although the unadjusted data showed few differences; MMF also tended to increase adjusted cortical bone and to reduce bone marrow adiposity and serum RANKL levels. Because these results suggest the possibility that MMF might be beneficial for bone, further investigation seems warranted.